2015
DOI: 10.1158/0008-5472.can-13-3426
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of Myosin-Dependent Contractility Sensitizes Glioma Tumor-Initiating Cells to Mechanical Inputs and Reduces Tissue Invasion

Abstract: Tumor-initiating cells (TICs) perpetuate tumor growth, enable therapeutic resistance, and drive initiation of successive tumors. Virtually nothing is known about the role of mechanotransductive signaling in controlling TIC tumorigenesis, despite the recognized importance of altered mechanics in tissue dysplasia and the common observation that extracellular matrix (ECM) stiffness strongly regulates cell behavior. To address this open question, we cultured primary human glioblastoma (GBM) TICs on laminin-functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 47 publications
4
68
0
Order By: Relevance
“…Indeed, melanoma tumor-repopulating cells preferentially self-renew on soft substrata in a Sox2-dependent manner (48). In contrast, glioblastoma tumor-initiating cells are insensitive to matrix mechanics, and enhancing their cytoskeletal contractility causes a loss of their tumor-promoting properties (49). In the breast, mechanosensing and mechanotransduction are altered as a function of aging (50), so the effects of stiffness on CSCs likely also depends on age.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, melanoma tumor-repopulating cells preferentially self-renew on soft substrata in a Sox2-dependent manner (48). In contrast, glioblastoma tumor-initiating cells are insensitive to matrix mechanics, and enhancing their cytoskeletal contractility causes a loss of their tumor-promoting properties (49). In the breast, mechanosensing and mechanotransduction are altered as a function of aging (50), so the effects of stiffness on CSCs likely also depends on age.…”
Section: Discussionmentioning
confidence: 99%
“…When Cav1 is overexpressed or re-expressed in Ha-Ras V12 transformed cells, stiffness sensing is restored; when knocked down, cells soften, their stiffness is not dependent upon substrate rigidity, and they are able to grow on soft substrates. Additionally, tumor-initiating cells or cancer stem cells are largely insensitive to stiffness with respect to spreading, migration, and proliferation, but can regain their stiffness response when myosin-dependent contractility is increased [7 •• ]. However, the generalization that cancer cell proliferation is stiffness-independent cannot be applied to all cancer types.…”
Section: Effects Of Mechanics On Proliferation and Apoptosismentioning
confidence: 99%
“…For example, this approach could allow correction or control of mechanically-driven cell behavior in instances where inserting a scaffold or otherwise modifying the extracellular environment is impractical or impossible. Proof-of-principle experiments have shown that genetic[18], chemical[37] and optical[44,45] actuation of signals can control cell mechanobiology in animal models to achieve clinically relevant goals, such as targeted immune cell recruitment or reduced cancer cell invasion. A challenging but critical next step will be to explore the use of these approaches in living organisms, with an eye towards eventual clinical use.…”
Section: Resultsmentioning
confidence: 99%
“…These features can be leveraged to study and control the biomechanical role of target proteins in mice grafted with genetically engineered cells. [18] However, there are also a number of limitations, perhaps the most important of which is the slow dynamics of the expression system and the protein of interest. While in some scenarios, cells respond phenotypically within six hours[16,19], some systems may take as long as ten days to reach a steady-state response[19,20].…”
Section: Controlled Induction Of Gene Expressionmentioning
confidence: 99%